Daya Hambat Ekstrak Kulit Semangka (Citrullus lanatus) Terhadap Pertumbuhan Candida albicans - Nindya Nur Maghfiroh; Ayu Mashartini Prihanti; Purwanto Purwanto (UPT Percetakan dan Penerbitan Universitas Jember, 2021)
Candida albicans is normal flora found in the oral mucosa in healthy individuals but has opportunistic pathogenic properties. The change in the oral cavity's environmental conditions can cause C. albicans to turn into a pathogen and cause oral candidiasis. Antifungal drugs that are common used for the treatment of oral candidiasis are topical nystatin preparations. Nystatin is an antifungal drug from the polyene group produced by Streptomyces noursei, which is thought to be very effective in treating diseases caused by C. albicans with a success rate 79.6 - 87.5%. The previous study showed that watermelon peel extract contains active compounds of alkaloids, flavonoids, tannins, and saponins. The active compound is known to have antifungal activity. The study aimed to determine the ability of watermelon peel extract to inhibit the growth of C. albicans. The type of research conducted is experimental laboratories using the post-test only control group design. The observations in this study about the inhibitory power of watermelon rind extract (Citrullus lanatus) on the growth of C. albicans showed that there were inhibitory zones of watermelon skin extract on the growth of C. albicans.